OPPORTUNITIES AND CHALLENGES OF MANDATORY SOCIAL SECURITY PARTICIPATION FOR INDONESIAN MIGRANT WORKERS: A REVIEW OF CONVENTIONAL LAW AND ISLAMIC LAW - Yefrizawati, Yefrizawati; Agusmidah, Agusmidah; Affila, Affila; Chairi, Zulfi; Khairunnisa, Siti; Alpani Pane, Farhan (NOMOI Law Review, 2024)
In developed countries, social security is a priority. So much so that social security is one of the administrative requirements that must be fulfilled by every citizen. Social security, especially for workers, should be placed on a primary scale because its function can help ensure the welfare of workers in the future. Indonesia is the country with the largest number of Muslims, but the development of social security is far behind, even though Islam has rules, including regarding social relations which are based on the concept of mutual help as contained in the zakat regulations. This situation is an opportunity, the obstacle lies in state regulations which do not yet require Indonesian Migrant Workers (PMI) to be participants in all existing programs, only requiring Accident Insurance (JKK) and Death Insurance (JKM), while Old Age Insurance/Pension Insurance (JHT) is optional. Another thing is that it is not easy for PMI who have worked in other countries to become participants, especially those who do not have a written contract, because one of the requirements is the existence of a written contract. This was complained about by PMI who worked in Malaysia through the forgiveness program from the Malaysian government. Using qualitative research methods, this research places the researcher as the key instrument. The data collection technique was carried out by combining results obtained through interviews, observation and literature study, combined with inductive data analysis.